2018
DOI: 10.1016/j.mayocpiqo.2017.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, Biochemical, and Radiological Characteristics of a Single-Center Retrospective Cohort of 705 Large Adrenal Tumors

Abstract: ObjectiveTo characterize large adrenal tumors (≥4 cm in diameter) and to identify features associated with malignancy.Patients and MethodsWe investigated the clinical, biochemical, and imaging characteristics in a large retrospective single-center cohort of patients with adrenal tumors of 4 cm or more in diameter during the period of January 1, 2000, through December 31, 2014.ResultsOf 4085 patients with adrenal tumors, 705 (17%) had adrenal masses measuring 4 cm or more in diameter; of these, 373 (53%) were w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
55
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(65 citation statements)
references
References 25 publications
6
55
1
3
Order By: Relevance
“…There were 111 cases of abdominal pain and/or palpable abdominal mass as symptoms at diagnosis (59.4% of known information), which is a higher rate than previous studies. Iñiguez-Ariza et al reported the mode of ACC discovery as follows: 42% incidentally found, 32% hormone excess, and 20% mass effect (29). Several patients reported no symptoms even when the mass was larger than 8 cm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There were 111 cases of abdominal pain and/or palpable abdominal mass as symptoms at diagnosis (59.4% of known information), which is a higher rate than previous studies. Iñiguez-Ariza et al reported the mode of ACC discovery as follows: 42% incidentally found, 32% hormone excess, and 20% mass effect (29). Several patients reported no symptoms even when the mass was larger than 8 cm.…”
Section: Discussionmentioning
confidence: 99%
“…Iñiguez-Ariza et al . reported the mode of ACC discovery as follows: 42% incidentally found, 32% hormone excess, and 20% mass effect ( 29 ). Several patients reported no symptoms even when the mass was larger than 8 cm.…”
Section: Discussionmentioning
confidence: 99%
“…These tumours account for 2–12% of adrenal incidentalomas. 10 , 11 , 12 , 13 Prognosis of ACC is poor and cure is achievable only with early detection and surgery. 14 Multimodal and repeated imaging is routinely used to detect and exclude ACC, despite an insufficient evidence base to support this approach due to small studies in heterogeneous populations and with poor reference standards.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, this cut-off of 4 cm to delineate potential malignancy (34%–61% specific) is challenged by Iniguez et al , in which only 31% of adrenal tumours above 4 cm were malignant. However, two notable risk factors for malignancy in this study were larger tumour size (7 cm) and non-incidental mode of discovery, suggesting that imaging still serves an integral role in the evaluation of adrenal tumours 10–12. Additionally, we utilised radiological guidance in the form of a CT-guided biopsy to ascertain a tissue diagnosis for our patient prior to surgical resection.…”
Section: Discussionmentioning
confidence: 98%